PENGARUH FAKTOR INTERNAL MAHASISWA DALAM MENGAMBIL KEPUTUSAN BERWIRAUSAHA DI INSTITUT BISNIS DAN INFORMATIKA STIKOM SURABAYA - Santoso, Rudi (Universitas PGRI Adi Buana, 2017)
One solution to reduce unemployment is by creating many job vacancies. Creating job opportunities must be started as early as possible at school. Therefore, the government instituted the structured model for education within entrepreneurship class. The purpose of this study was to determine the extent of students’ internal factors, such as interest, self-empowerment, and motivation, influencing them on making decision to be an entrepreneur. This study took the sample from the students of Institute of Business and Informatics Stikom Surabaya who have run a business or who have planned to start their own business. The total of collected sample was forty-two respondents. This study employed cluster random sampling to choose the respondent. Conclusion: This study proved that the internal factors, such as interest, self-empowerment, and motivation contributes 50,8% for influencing students to decide to be an entrepreneur. F statistics test result showed 0,000 < 0, 05; thus, it can be implied that variable X (Interest, Self-empowerment, and Motivation) influenced Y (students’s decision to be an entrepreneur.) Keywords: entrepreneur, entrepreneurship, business